2018
DOI: 10.1097/aln.0000000000002045
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation before Debriefing during High-fidelity Simulation Improves Memory Retention of Residents at Three Months

Abstract: Background High-fidelity simulation is known to improve participant learning and behavioral performance. Simulation scenarios generate stress that affects memory retention and may impact future performance. The authors hypothesized that more participants would recall three or more critical key messages at three months when a relaxation break was performed before debriefing of critical event scenarios. Methods Each resident ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, other studies reveal that simulated settings can elicit a high degree of immersion, and also stress [89,90].…”
Section: Immersion In the Assessment Situation When Using Sps And Rpsmentioning
confidence: 98%
“…However, other studies reveal that simulated settings can elicit a high degree of immersion, and also stress [89,90].…”
Section: Immersion In the Assessment Situation When Using Sps And Rpsmentioning
confidence: 98%
“…Recent advances made it possible to overcome the limitations of standard laboratory tasks by implementing virtual reality or high-fidelity simulations (also called full scale simulations). Simulation environments enable situations still closer to real-life along with experimental control, hence allowing investigation of the direct effects of stress on professional performance 17 – 22 . Simulation studies usually focus on urgent and crucial professional situations, such as the management of critical care for anaesthetists 20 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Simulation environments enable situations still closer to real-life along with experimental control, hence allowing investigation of the direct effects of stress on professional performance 17 – 22 . Simulation studies usually focus on urgent and crucial professional situations, such as the management of critical care for anaesthetists 20 22 . These simulations remain indispensable for training anesthesiology residents to practice in one of the most stressful medical professions 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study compared the difference in performance between the use of a digital CA and memory using the same protocol, which is the reference of care within the French Army, in simulated high-stakes crisis situations that can hamper decision making [28][29][30] and access to known information. 28 We found that the use of the digital CA improved performance on a set of preplanned observations and tasks, without testing the leader's problem-solving abilities, in scenarios designed to test the ability to perform immediate, short-term, standard lifesaving actions, rather than to establish a strategic care plan for patient management.…”
Section: Discussionmentioning
confidence: 99%